Predictors of Resilience among the Parents of Children with Cancer (Caring: Indonesian Journal of Nursing Science, 2023)
The experience of caring for children with cancer is challenging and may lead to a traumatic experience for parents. Research has shown that resilience supports parents in dealing with psychological problems during the cancer treatment process. This study aims to identify the factors that influence the resilience of parents of children with cancer. The research involved 63 parents/caregivers of children with cancer. The research instruments used were a demographic questionnaire, the Connor Davidson Resilience Scale (CD-RISC 25), and the Multidimensional Scale of Perceived Social Support (MSPSS). Linear regression analysis was used to determine the most dominant factors affecting resilience in parents/caregivers of children with cancer. The results showed that the mean score of resilience for parents/caregivers of children with cancer was 67.55 Â± 10.89. It was found that factors associated with resilience were social support (Ï=0.00) and time since children were diagnosed with cancer (Ï=0.02). The most dominant factor influencing resilience is social support (Î² value = 0.10). Therefore, health workers are expected to be able to facilitate social support for parents of children with cancer to increase resilience.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â